Why forcing people to save for retirement may backfire - Monika Buetler; Olivia Huguenin; Federica Teppa (Center for Economic Studies and ifo Institute (CESifo), 2005)
If individuals are unable or unwilling to borrow, a higher than desired second pillar pension capital may induce people to retire earlier than they would have in the absence of such a scheme. Individuals thus leave the workforce as soon as the retirement income is deemed sufficient and the pension plan avails withdrawal of benefits. We provide evidence using individual data from a selection of Swiss pension funds, allowing us to perfectly control for pension scheme details. Our findings suggest that affordability is a key determinant in the retirement decisions. The higher the accumulated pension capital, the earlier individuals tend to leave the workforce.
Keywords: H31; D91; J26; 330; occupational pension; retirement decision; duration models; Altersgrenze; Alterssicherung; Sparen; Pensionsfonds; Arbeitsangebot; Schätzung; Schweiz